中国网络流行语在新加坡的传播与使用情况——以《咬文嚼字》年度十大流行语为例 = The spread and use of China's internet buzzwords in Singapore - 卢纬霖 Loo, Wei Lin (Nanyang Technological University, 2023)
互联网与社交媒体的发展形成了一种新颖且特殊的语言形式，即网络语言。网络流行语是网络语言的一种语言形式，可定义为某一段时期在网络上受人们广泛使用以及传播，具有时代性的语言形式。网络流行语在中国是极为普遍的现象，尤其在于年轻群体当中。网络流行语目前的研究着重于中国社会。众多学者对网络流行语进行了研究，如网络流行语的类型与特征、传播与变迁以及使用情况。少数的研究者在中国以外展开网络流行语的调查或将中老年群体包括在调查对象当中。在新加坡，则没有学者针对网络流行语的使用进行实证调查研究。笔者希望填补网络流行语研究的空缺，因此通过问卷调查的方式，并以年龄层与时间段的角度探讨新加坡网络流行语的传播与使用情况、态度与其因素。本研究发现，青年和中老年这两个年龄组的调查对象都对实用性高的网络流行语认知度高，对与中国政策相关的流行语认知度低，对形式简单的流行语理解度高。另外，本研究的结果显示了网络流行语认知度、理解度与使用度之间的可能关系——较低的认知度导致较低的理解度，从而降低使用度。其次，两个年龄组对于早期的网络流行语认知度、理解度与使用度较高，且青年组在这三方面的程度都比中老年组的更高。本研究发现这些现象与网络因素以及与中国媒体或亲友的接触有可能的关系。 最后，两组对网络流行语的态度都较为积极，但青年组比中老年组的表现更加为乐观，支持也更为强烈。笔者希望这项调查研究能够为新加坡网络流行语的各别情况提供价值性的参考，对新加坡语言方面的研究作出贡献。关键词:网络流行语;实证研究;使用情况;新加坡华语 The development of the Internet and social media has created a new and distinct language form, Internet language. Internet buzzwords are a form of Internet language, which can be defined as a language form that is widely used and disseminated on the Internet during a certain period of time. They are extremely common in China, especially among the younger generation. Current research on Internet buzzwords focuses on China’s society, and many scholars have conducted research on the types and characteristics of Internet buzzwords, their dissemination and changes, and their usage. Very few researchers conducted surveys on Internet buzzwords outside of China or included middle-aged/elderly groups in their targeted groups. In Singapore, no scholars have conducted empirical research on the use of Internet buzzwords. The author hopes to fill up current research gaps in this area. Hence in this research, a questionnaire survey was conducted, targeting the young and middle-aged/elderly groups and discussing the spread and use of Internet buzzwords in Singapore and the attributing factors to related trends from the perspectives of age group and time period. This study found that respondents in both age groups have higher degree of cognition towards Internet buzzwords that are practical in terms of use and lower degree of cognition towards buzzwords related to China's policies. Respondents from both age groups also have higher degree of understanding towards buzzwords that come in simpler forms. In addition, the results of this study show a possible relationship between degree of cognition, understanding and usage of Internet buzzwords, that is, lower degree of cognition leads to lower degree of understanding, which in turn leads to lower usage. Moreover, the study also found that both age groups have a higher degree of cognition, understanding and usage of Internet buzzwords from the earlier period, and in these three aspects, the results from the youth group is shown to be higher than that of the middle-aged/elderly group. This study found that these phenomena may be related to network factors and contact with China’s media or Chinese relatives and friends. Also, both groups were found to have positive attitudes towards Internet buzzwords, but the youth group showed stronger optimism and support. The author hopes that this investigation and research can provide valuable references for the individual situations of Singaporean Internet buzzwords and contribute to the study of Singaporean language. Keywords: Internet Buzzwords; Empirical Research; Usage Situation; Singapore Mandarin